Desafios da reestruturação do ensino médio no Estado do Amazonas - Oriente, Silvana Barreto (Universidade Federal de São Carlos, 2025)
This research investigates the challenges of restructuring secondary education in the state of Amazonas, with the general aim of analyzing the tensions present in the process of implementing the policy, based on the perceptions of educators and managers from different regions of the state. In addition to the difficulties inherent to regional specificities, such as geographical distance and limited access, the research highlights the internal, ethnic and racial diversity of the Amazonian territory as an aspect that is little considered in the formulation and implementation of educational policy. The research is driven by the following question: how can we guide the implementation of a public education policy that takes territorial diversity as a reference and starting point? The thesis was built along three main lines: (1) a bibliographical survey of the latest high school reforms in Brazil; (2) the characterization and analysis of the proposal to restructure high school in the state of Amazonas; and (3) the comparison between this proposal and the perceptions of teachers and managers in the various regions of the state. Through these paths, the research seeks to contribute to reflection on educational policies that dialogue with the socio-cultural contexts in which they are implemented, recognizing diversity as a structuring element of educational provision. The methodological choices are based on post-critical studies in education, as proposed by Meyer and Paraíso (2021). Based on a qualitative approach, it combines documentary analysis with a bibliographical review, followed by dense field research, carried out in at least one municipality in each channel of the main rivers in the Amazon, through re-signified narrative interviews (Andrade, 2012) with educators who work in secondary education in the state of Amazonas.The theoretical framework that underpins the research is based on approaches that dialog with post-critical theories in education, such as cultural, decolonial and ethnic-racial studies.The data analysis was organized into five main axes: general infrastructure; pedagogical and teaching structure; teacher training; student protagonism and indigenous education.The main findings indicate that the restructuring of secondary education in Amazonas has taken on worrying contours due to the profound territorial, social and cultural inequalities that mark the interior of the Amazon region, which were not considered at the time of implementation of this important public policy.
Challenges of restructuring secondary education in the State of Amazonas
Keywords: Políticas Públicas Educacionais; Ensino médio; Diversidade; Currículo; Juventudes; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; 18. Igualdade Étnico-Racial para o Desenvolvimento Sustentável